Long-term excess mortality associated with diabetes following acute myocardial infarction: a population-based cohort study. Issue 1 (15th June 2016) - Alabas, O A; Hall, M; Dondo, T B; Rutherford, M J; Timmis, A D; Batin, P D; Deanfield, J E; Hemingway, H; Gale, C P
Abstract : Background: The long-term excess risk of death associated with diabetes following acute myocardial infarction is unknown. We determined the excess risk of death associated with diabetes among patients with ST-elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI) after adjustment for comorbidity, risk factors and cardiovascular treatments. Methods: Nationwide population-based cohort (STEMI n=281 259 and NSTEMI n=422 661) using data from the UK acute myocardial infarction registry, MINAP, between 1 January 2003 and 30 June 2013. Age, sex, calendar year and country-specific mortality rates for the populace of England and Wales (n=56.9 million) were matched to cases of STEMI and NSTEMI. Flexible parametric survival models were used to calculate excess mortality rate ratios (EMRR) after multivariable adjustment. This study is registered at ClinicalTrials.gov (NCT02591576 ). Results: Over 1.94 million person-years follow-up including 120 568 (17.1%) patients with diabetes, there were 187 875 (26.7%) deaths. Overall, unadjusted (all cause) mortality was higher among patients with than without diabetes (35.8% vs 25.3%). After adjustment for age, sex and year of acute myocardial infarction, diabetes was associated with a 72% and 67% excess risk of death following STEMI (EMRR 1.72, 95% CI 1.66 to 1.79) and NSTEMI (1.67, 1.63 to 1.71). Diabetes remained significantly associated with substantial excess mortality despite cumulative adjustment for comorbidity (EMRR 1.52, 95% CI 1.46 to 1.58 vs 1.45, 1.42 to 1.49), risk factors (1.50, 1.44 to 1.57 vs 1.33, 1.30 to 1.36) and cardiovascular treatments (1.56, 1.49 to 1.63 vs 1.39, 1.36 to 1.43). Conclusions: At index acute myocardial infarction, diabetes was common and associated with significant long-term excess mortality, over and above the effects of comorbidities, risk factors and cardiovascular treatments.